Capital Punishment and Lethal Assaults Against Police - Bailey, William C. (1982)
This investigation provides a multivariate analysis of the deterrent effect of the death penalty on the rate of lethal assaults against the police. Examining state level data for the period 1961 to 1971, we hypothesize a significant inverse relationship between the rate of police killings and (1) the statutory provision for capital punishment and (2) the execution rate of convicted murderers. Contrary to the deterrence hypotheses, no support is found for the argument that the provision and use of the death penalty provides an added measure of protection for the police. Rather, variation in police killings rates, like the general homicide rate, would appear to be largely a function of various sociodemographic factors